AC electric field induced droplet deformation in a microfluidic T-junction. Issue 16 (13th May 2016) - Xi, Heng-Dong; Guo, Wei; Leniart, Michael; Chong, Zhuang Zhi; Tan, Say Hwa
Abstract : We present a novel method for the deformation of droplets in a microfluidic T-junction using an AC electric field. Abstract : We present for the first time an experimental study on the droplet deformation induced by an AC electric field in droplet-based microfluidics. It is found that the deformation of the droplets becomes stronger with increasing electric field intensity and frequency. The measured electric field intensity dependence of the droplet deformation is consistent with an early theoretical prediction for stationary droplets. We also proposed a simple equivalent circuit model to account for the frequency dependence of the droplet deformation. The model well explains our experimental observations. In addition, we found that the droplets can be deformed repeatedly by applying an amplitude modulation (AM) signal.